Cotton certification in Sub-Saharan Africa: Promotion of environmental sustainability or greenwashing?. (July 2019) - Partzsch, Lena; Zander, Macy; Robinson, Hannah
Highlights: Cotton production in SSA causes a number of environmental sustainability challenges. Voluntary certification programs aim to influence corporate conduct along supply chains. The EU Organic Standard is most ambitious in addressing NGOs' environmental demands. NGOs risk contributing to 'greenwashing' when participating in less ambitious programs. Abstract: Environmental sustainability is a major challenge for cotton production in Sub-Saharan Africa (SSA). The creation of voluntary certification programs is an effort aimed at finding new ways to influence corporate conduct along supply chains. This article contributes novelty and insight on cotton certification in SSA by exploring the most relevant programs in detail with regard to the demands of international non-governmental organizations (NGOs). We selected the five most central NGOs dedicated to environmental sustainability in agriculture: Friends of the Earth (FoE), Greenpeace, Oxfam, Pesticide Action Network (PAN), and World Wildlife Fund (WWF). After identifying these NGOs' demands regarding pesticides, fertilizers and genetically modified (GM) cotton, we analyzed the requirements of the four most dominant programs certifying SSA cotton cultivation: the Better Cotton Initiative (BCI), Cotton made in Africa (CmiA), the EU Organic Regulation and Fairtrade Labelling Organization (FLO). The results of our document analysis are bolstered by semi-structured interviews with stakeholders on NGOs' stances and roles in standard setting and implementation. We find that the EU Organic Regulation scores best in terms of environmental sustainability. Those programs in which NGOs actively participate are less ambitious compared to the public standard. Therefore, we conclude that, if NGOs maintain their commitment to multi-stakeholder initiatives, they risk contributing to 'greenwashing' corporate conduct by mobilizing consumer support for labelling programs that actually fall behind existing public regulation on organic certification.